Spectroscopic Diagnostics of Exploding Aluminum Wire Plasma in Distilled Water - Hashim, Hassan (Al-Nahrain Journal of Science, 2018)
This work aims to study the exploding aluminum wire plasma parameters by using optical emission spectroscopy method. The emission spectra of the aluminum discharge plasma have been recorded and analyzed. The plasma electron temperature (Te) was calculated by Boltzmann plot, and the electron density (ne), by Stark broadening for aluminum wire of diameter 0.3 mm and different current 75,100, and 160A in distilled water. The aluminum line 656.279 nm was used to calculate the electron density by Stark broadening. It was found that the electron density (ne) increase from 28×1016cm-3 to 60×1016 cm-3 with increasing current from 75 to 160 A, while the electron temperatures increase from 0.986 to 1.614 eV for the same conditions. The optical emission spectrum (OES) emitted from the plasma have a peak located at 653 nm corresponding to Hα line for hydrogen atoms, and others peaks belong to Aluminum (AlI and AlII lines), and Oxygen (OI and OII lines). The relationship between the plasma electron temperature, emission line intensity and number density were studied.